(untitled) (Research, Society and Development, 2020)
This work seeks to describe the experience of the members of the Education through Work for Health - Interprofessionality and Mental Health Program in the construction of informative materials directed mainly to mental health care in the face of the OVID-19 pandemic. It is an experience report on the production process of booklets and folders held in early March 2020, edited and disseminated from March to April 2020, aimed at the external community in general, also including health professionals. This work was developed in a collective and collaborative manner, highlighting the promotion of mental health of the general population and the collective involved in the production of the materials itself, as well as strengthening the support network among project members. Based on this experience, it is possible to observe the importance of actions responsible for the articulation between the Health Care Network and the University, thus strengthening the teaching- service-community relationship.